Fluência em leitura oral, compreensão e hábitos de leitura: influência da leiturabilidade no desempenho em textos narrativos e informativos - MOUTINHO, Michell Gadelha (Universidade Federal do Pará, 2025)
This research aims to investigate, from two dimensions of oral reading fluency (rate and accuracy), the performance of 6th and 9th graders from public and private schools from Belém in reading narrative and informative texts (extracted from textbooks adequate for both grades) with different Readability levels. Moutinho (2016) noticed in his research that students’ performances in relation to accuracy in oral reading of both types is distinct, confirming previous researches (PAIGE et al., 2015). To evaluate more deeply these performances, it was used Curriculum-based measurement (CBM), which states that 1-minute oral reading is enough to assess global performance in reading. However, it was necessary to establish if the texts used to the assessment were actually adequate to the development level of students. Moutinho e Picanço (2022) observed that there is a great difference in textual complexity in texts from textbooks used for 5th to 9th grades. Considering this, in order to manage to more reliably evaluate students’ performance, the Flesch Readability Index was used, adapted to Portuguese (MARTINS et al., 1996) with the tool Coh-Metrix (SCARTON; ALUÍSIO, 2010). The research was conducted in seven schools from Belém’s metropolitan region, four private and three public schools. Each student read two narrative and two informative texts, one simpler and another more complex from each type, according to the Flesch Index. Moreover, to measure students’ comprehension, at the end of each oral reading, participants retold what they had read in the texts and also told, in a semi-structured interview, their reading habits. Results were divided according to the different tasks. To assess reading rate and accuracy, it was observed that both grades are below the stipulated level set up by research and official institutions. There was a difference between narrative and informative text reading for the 6th grade, whereas for the 9th grade the differences were inverted, as the complex texts been read with better performance than the simple ones. In the comprehension task, results show that many of the students had difficulty in retelling what they had read, especially for the 9th grade, which mentioned less propositions than the 6th grade. Regarding the reading habits, most of the students from both grades stated they read at home and are encouraged to read. Both the comprehension task and the statements from reading habits interview had no statistically significant correlation with their performance related to the accuracy performance, though data may suggest possibilities for intervention which can encompass all three variables, so that they promote development in reading performance.